1995
DOI: 10.1055/s-2007-996544
|View full text |Cite
|
Sign up to set email alerts
|

Lagerungsschäden beim Patienten mit unbekanntem „thoracic outlet syndrome”

Abstract: Following a 3-hour surgery of his left leg, a 22 year old male patient suffered paralysis and burning pain in his left forearm with numbness of his 3rd, 4th and 5th finger. During the following days the symptoms diminished spontaneously. The explanation is an ischaemia due to the positioning during the operation in presence of an unknown thoracic outlet syndrome. Diagnostic procedure and prophylaxis of the disease are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
4
0
4
Order By: Relevance
“…VI ZR 60/ 94; VersR 1995, 539) is not contrary to the obligation to inform the patient of the possible risk of positioning injuries [16,17], because even technically perfect positioning cannot prevent pressure injury. In the above ruling of January 24,1984, in which the BGH referred the procedure back to the appeals court for a fresh ruling, the BGH indicated that the appeals court would also have to investigate the issue "whether the consent to the operation given by the plaintiff could be invalid because of insufficient information about the risk of positioning injuries." Accordingly, most currently available commercial information and medical history sheets include the risk of positioning injury as part of the information provided to patients [18].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…VI ZR 60/ 94; VersR 1995, 539) is not contrary to the obligation to inform the patient of the possible risk of positioning injuries [16,17], because even technically perfect positioning cannot prevent pressure injury. In the above ruling of January 24,1984, in which the BGH referred the procedure back to the appeals court for a fresh ruling, the BGH indicated that the appeals court would also have to investigate the issue "whether the consent to the operation given by the plaintiff could be invalid because of insufficient information about the risk of positioning injuries." Accordingly, most currently available commercial information and medical history sheets include the risk of positioning injury as part of the information provided to patients [18].…”
Section: 2mentioning
confidence: 99%
“…Neuropathy, pressure ulcer Age > 70 years [20] Neuropathy, pressure ulcer Malnutrition [22] Pressure ulcer Peripheral arterial occlusive disease Neuropathy Smoking and COPD [12,22,23] Neuropathy of the lower extremities, pressure ulcer Anatomical abnormality (cervical rib, etc.) [24] Neuropathy Pre-existing neuropathies [12] Neuropathy, pressure ulcer Table 3 Surgical factors associated with an increased risk of positioning injury.…”
Section: Positioning-related Neuropathiesmentioning
confidence: 99%
“…Vermutet man eine Nervenschädigung, wird eine klinische und elektrophysiologische Untersuchung durch einen Neurologen veranlasst. Nicht ganz selten lassen sich retrospektiv anatomische Varianten oder präexistente Neuropathien als Mit− verursacher eruieren [16,26].…”
Section: Schlussbemerkungunclassified
“…Zwar lassen sich lagerungsabhängige Störungen der Durchblu− tung bei bestimmten Syndromen durch Provokationstests erfas− sen. So führt beim Thoracic−outlet−Syndrom die Hyperextension des Kopfes mit Seitwärtsdrehen des Kinns zur kranken Seite (Ad− son−Manöver) neben Sensibilitätsstörungen zu einer Kompres− sion der A. subclavia mit Abschwächung des Radialispulses[26]. Ähnliche Symptome lassen sich beim Hyperabduktions−Syn− drom durch Hochheben des Armes über die Waagerechte auslö− sen. Hier würde sich die ¹Über−Kopf"−Lagerung des Patientenar− mes verbieten.…”
unclassified
“…Alternativ zur SPA für Eingriffe in Bauchlage werden die Periduralanäs-lich 4 Personen, der zur Umlagerung von intubierten Patienten in die Bauchlagerung notwendig ist, sind hierbei auch kardiozirkulatorische Nebenwirkungen [3] und in Einzelfällen sogar respiratorische Probleme beschrieben worden [4,39] [35]. Es gibt zur Inzidenz von Nervenschäden nach Bauchlagerung in der Literatur trotz einiger guter Übersichtsartikel [24,47] keine genaue Zahlen, und es ist zu befürchten, daß eine relativ hohe Dunkelziffer an unerkannten oder passageren nervalen Beeinträchtigungen existiert.…”
Section: Ist Die Periduralanästhesie Eine Alternative?unclassified